IN WORK OF MRAYAM QUDRAT ASEEL PATRIARCHAL SUPREMACY AND ITS VISUAL EXPRESSION - Begimkulova Shaxnoza Axmedovna (Journal of new century innovations, 2024)
Abstract. The research purpose to clearify the role of women in the patriarchal family. In the Afghan-American literature that we analyzed, the concept of values is covered in a wide scope. Among the Afghan-American writers who are the object of our research is Maryam Qudrat Aseel (“Torn Between Two Cultures: an Afghan- American Woman Speaks Out”) was analyzed literary-artistically based on national and universal values. In this work, the values are interpreted from human, national, and family perspectives, and they show the unique qualities, virtues, and wisdom of the Afghan nation, which is reflected in national pride. In other words, the nation’s culture, faith, national traditions, and aspects of national education are manifested in their unique values. Throughout the article, there is given themes related to Islamic culture and identity, such as gender roles, family dynamics, and the impact of political events on the Muslim community. Article emphasizes the importance of cultural understanding and empathy, both within the Muslim community and between different cultural groups.